Kebutuhan Koleksi Perspektif Pemustaka Perpustakaan Universitas Islam Negeri Sultan Syarif Kasim Riau - Rasdanelis Rasdanelis; Eko Syahputra; Supliadi Supliadi (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This research discusses the collection needs of UIN Sultan Syarif Kasim Riau library users' perspective. This research aims to describe and analyze the collection needs from the perspective of the library users of UIN Sultan Syarif Kasim Riau library. Research on library users' collection needs is considered important to do, as an evaluation tool and reference for libraries in developing collections. This research uses descriptive research methods with quantitative approach. The research data was collected through questionnaires, observation and documentation. Based on the results of the study, it was revealed that UIN Sultan Syarif Kasim Riau library users expect quality and up-to-date collections, including textbooks, references and journals/series in various forms, both print and electronic. From the data analysis, that the user's need for textbooks, references, and journals in various forms, both printed and electronic, with a variable score of user collection needs reaching 91%. It’s means that the user's need for collections in various types and forms, both printed and non-printed (electronic) is included in the very high category.